CSC562: Information Retrieval and Searching Algorithms / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
This course intends to prepare students a basic background concerning the automated storage and retrieval of information. Text is the primary way that human knowledge is stored, and after speech, it is the primary way of transmitted data to one and another. This course will mainly focus on the techniques for storing, searching and retrieving for textual documents. Both the theoretical aspects of information retrieval design and evaluation and the practical aspects of how these theories have been implemented in actual systems will be covered. Other types of IR, such as web retrieval, web crawling and multimedia IR will be introduced as an exposure to different types of IR besides text IR